Research on end-edge-cloud collaborative model of smart home system. (19th June 2023) - Lu, Shun-Kai; Fu, Bao-Chuan
By introducing edge computing technology, an end-to-end cloud collaborative task scheduling model is built to provide computing power support for smart home systems. With the purpose of increasing the utilisation rate of edge nodes and sharing the cloud computing pressure as well as meeting the demand of users for time delay as the constraint condition, tasks generated by users are analysed and offloaded to each edge node and cloud according to greedy algorithm. The edge nodes are pre-graded to reduce the global neglect of greedy algorithm when it comes to local optimal solution. The optimisation of setting edge node pair to reduce cloud platform pressure and edge node hierarchical offloading compared with traditional computing mode is verified by simulation.